2007
DOI: 10.1161/atvbaha.107.142695
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Levels of Oxidized Low-Density Lipoprotein Prime Monocytes to Cytokine Overproduction via Upregulation of CD14 and Toll-Like Receptor 4 in Unstable Angina

Abstract: Objectives-The purpose of this study was to establish whether oxidized low-density lipoprotein (oxLDL) contributes to cytokine overproduction via upregulation of CD14 and toll-like receptor-4 (TLR-4) expression on circulating monocytes of unstable angina (UA) patients. Methods and Results-Expression of CD14 and TLR-4 on circulating monocytes, and the concentration of plasma oxLDL, (interleukin [IL])-6, IL-1 beta, IL-8, tumor necrosis factor (TNF)-alpha, monocyte chemoattractant protein-1 (MCP-1) were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
4
36
0
5
Order By: Relevance
“…Moreover, compared with the control group, mice with both myeloid differentiation factor 88 (MyD88), which is the downstream gene of TLR4, and ApoE knocked out showed a 60% reduction of the plaque area. Another study (Pasini et al, 2007) found that MCP-1 and other inflammatory cytokines that were excessively expressed in patients with unstable angina might be related to the oxLDL-induced up-regulation of TLR4. RNA interference technology was used to block TLR4 to investigate the function and mechanism of TLR4 in the oxLDL-induced up-regulation of LOX-1, MCP-1, and VCAM-1 expressions in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with the control group, mice with both myeloid differentiation factor 88 (MyD88), which is the downstream gene of TLR4, and ApoE knocked out showed a 60% reduction of the plaque area. Another study (Pasini et al, 2007) found that MCP-1 and other inflammatory cytokines that were excessively expressed in patients with unstable angina might be related to the oxLDL-induced up-regulation of TLR4. RNA interference technology was used to block TLR4 to investigate the function and mechanism of TLR4 in the oxLDL-induced up-regulation of LOX-1, MCP-1, and VCAM-1 expressions in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2, TLR4, or TLR6 can also heterodimerize and interact with CD36 in a ligand-specifi c manner ( 54 ). Ox-LDL can also prime monocytes and peripheral blood mononuclear cell for cytokine overproduction by upregulating TLR2 and TLR4 ( 4,55,56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Standard curve was prepared for each assay run using calibrators and control supplied along with the assay kit. Cu 2+ -modifi ed LDL (50-500 ng/ml) was used as standard solution ( 4 ) to quantify the circulating plasma Ox-LDL in micrograms per milliliter for the treatment in primary monocytes isolated from healthy volunteers.…”
Section: Immunoprecipitation and In Vitro Kinase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it was determined that mmLDL is capable of binding to CD14 and that, through the TLR4/MD2 complex, mmLDL causes actin polymerization and membrane spreading in macrophages (Miller et al, 2002). However, it has been shown that mmLDL induces secretion of pro-inflammatory cytokines, such as IL-1 , IL-6, and TNF-, in human monocytes and macrophages through CD14 (Chávez-Sánchez et al, 2010a, Chávez-Sánchez et al, 2010b, which is corroborated by the fact that the blockade of CD14 with anti-CD14 antibodies significantly reduces the concentration of pro-inflammatory cytokines, including IL-1 and IL-6, produced by macrophages in response to oxLDL (Pasini et al, 2007). The stimulation of human monocytes and macrophages with mmLDL induces the secretion of IL-1 , IL-6, and TNFthrough a TLR4-dependent mechanism (Chávez-Sánchez et al, 2010a, Chávez-Sánchez et al, 2010b, which is similar to the mechanism by which end products of LDL glycosylation lead to the production of TNF- (Hodgkinson et al, 2008a).…”
Section: Role Of Tlrs In Response To Endogenous Ligands During Atheromentioning
confidence: 91%